FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KESEDIAAN IBU BERSALIN UNTUK PEMASANGAN IUD POST PLACENTA - Saiful Batubara; Risqi Utami (JURNAL ILMIAH DHDT - KEBIDANAN, 2019)
Intra Uterine Device post placenta is the installation in the first 10 minutes to 48 hours after the birth placenta plays a role in reducing maternal mortality through prevention of pregnancy, delaying pregnancy, and spacing pregnancies, the effectiveness of use up to 99.4% can prevent 5-10 years of pregnancy. This study aims to determine the factors associated with maternal willingness to post Post Placenta IUD. The study used a questionnaire with a population of third trimester pregnant women who examined their pregnancies and a sample of 98 people by purposive sampling. Analyze data with Chi Square. The results showed that the majority of pregnant women were not willing to do post placenta IUD installation of 58.2% which was influenced by age, parity, knowledge and support of the husband.